REFLECTED IN THE CONSOLIDATED FINANCIAL STATEMENTS BUSINESS COMBINATIONS - Makhmudova Nargiza Davlat qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
This article examines the theoretical and methodological aspects of reflecting business combinations in consolidated financial statements. In the context of increasing corporate integration and globalization, business combinations have become a key instrument for expanding economic activity and strengthening competitive positions. The study analyzes the economic substance of business combinations, the acquisition method prescribed by IFRS 3 “Business Combinations,” and the recognition and measurement of identifiable assets, liabilities, non-controlling interests, and goodwill in consolidated financial reporting. Special attention is paid to the process of determining the acquisition date, measuring fair value, recognizing goodwill or gain from a bargain purchase, and eliminating intra-group transactions in accordance with IFRS 10 “Consolidated Financial Statements.” The article also highlights the impact of business combinations on financial performance indicators, capital structure, and risk assessment at the group level.